2009
DOI: 10.1111/j.1755-0238.2008.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potential atmospheric warming on temperature-based indices describing Australian winegrape growing conditions

Abstract: Significance of the Study: Without appropriate adaptations, some established viticultural regions of Australia may become less suitable for quality winegrape production, whereas regions that were once considered unsuitable for quality winegrape production may become more suitable. Abbreviations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 18 publications
4
81
0
1
Order By: Relevance
“…The length of growing season is also a determining factor in grape composition (Jackson and Lombard 1993, Duchene and Schneider 2005, Webb et al 2007). Some authors confirmed that earlier ripening periods in a season may have negative effects on grape composition and, therefore, on wine quality Davis 2000, Hall andJones 2009). Furthermore, grape texture is linked to growing location, reflecting a terroir influence on grape quality (Le Moigne et al 2008a).…”
Section: Effects Of Climate Vintage and Growing Location On Texturementioning
confidence: 83%
See 1 more Smart Citation
“…The length of growing season is also a determining factor in grape composition (Jackson and Lombard 1993, Duchene and Schneider 2005, Webb et al 2007). Some authors confirmed that earlier ripening periods in a season may have negative effects on grape composition and, therefore, on wine quality Davis 2000, Hall andJones 2009). Furthermore, grape texture is linked to growing location, reflecting a terroir influence on grape quality (Le Moigne et al 2008a).…”
Section: Effects Of Climate Vintage and Growing Location On Texturementioning
confidence: 83%
“…The relationship between climate and berry properties has attracted considerable attention; temperature is recognized as the main climatic variable affecting vintage quality (Jackson andLombard 1993, Hall andJones 2009). Nevertheless, the impact of temperature on harvested grape quality can vary for different grapevine cultivars as a consequence of genotype-environment interaction.…”
Section: Effects Of Climate Vintage and Growing Location On Texturementioning
confidence: 99%
“…Therefore it is possible, for example that climate, disease and pest conditions in the Italian regions may become typical for South Germany in the future. Changes in the location and extent of areas suitable for viticulture are anticipated for the 21st century (White et al 2006, Hall & Jones 2009). Hall & Jones (2009), for example, expect that Australia will experience a decrease of areas suitable for high quality wines, since viticulture is close to reaching its southern limit on this continent, and there is no land to allow it to migrate further south.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the location and extent of areas suitable for viticulture are anticipated for the 21st century (White et al 2006, Hall & Jones 2009). Hall & Jones (2009), for example, expect that Australia will experience a decrease of areas suitable for high quality wines, since viticulture is close to reaching its southern limit on this continent, and there is no land to allow it to migrate further south. In Baden-Württemberg, a possible expansion of suitable areas for viticulture was observed by Stock (2005) using primarily a statistical regional climate model (SRCM) STAR.…”
Section: Introductionmentioning
confidence: 99%
“…Temperatures in wine regions worldwide have increased 1-3°C over the last 25 to 50 years Hall and Jones, 2009) and approximately 0.1°C/decade in New Zealand (Mullan et al, 2010), which would mean that the 1971-2000 climate normals used in this research should be updated to the next period normals once the data become available. For example, showed that GDD values from stations from the 1971-2000 climate normals in the western US were on average 10 % higher than those experienced during the middle of the 20th century.…”
Section: Discussionmentioning
confidence: 99%